Communication Strategy for Religious Counseling Counseling in Minimizing Divorce in Gunung Meria District, Aceh Singkil Regency - Gepeng Rambe; Zainun Zainun; Syawaluddin Nasution (Budapest International Research and Critics University, 2022)
The purpose of this study is to find out what counseling communication strategies are used by religious instructors in Gunung District, Aceh Singkil Regency to reduce divorce rates, as well as what follow-up steps they take to ensure the strategy has the desired effect. To conduct this qualitative study, the researcher interviewed a religious figure from Mount Meriah who he considered an expert in his field. Non-participant observations, interviews, and key documents were used to collect information about participants in the marriage counseling program, sakinah family, marriage counseling program, and other factors relevant to this research involved in the counseling process concurrently as priest and teacher. The consultation services provided are also still not effective due to the lack of people who are aware of the duties and functions of BP4 related to marriage consultation and fostering sakinah families. Researchers found that unmarried individuals who had previously been registered with the Office of Religious Affairs in Gunung Meriah Regency were the most likely to attend marriage counseling. Every bride-to-be is expected to feel more secure in their wedding plans after attending marriage counseling and receiving materials on topics such as: planning a wedding with a sakinah family; managing marriage and family dynamics; meet family needs; maintain family reproductive health; prepare the next generation for success; and managing conflict and building family resilience. Participants in the marriage mentoring program felt confident in their ability to continue their marriage, and the program also succeeded in meeting the needs of the bride and groom.